Diabetic Retinopathy: Current Understanding, Mechanisms and Treatment Strategies - Amjad, Mohd; Gupta, Harsh; Anamika; Kumar, Roshan; Kumar, Roshan (Journal for Research in Applied Sciences and Biotechnology, 2024)
Researchers have been assuming about the possible connection between the eye and the central nervous system (CNS) for a considerable amount of time. This is primarily due to the fact that the eye is considered to be an extension of the brain, which is a reasonable assumption. The neural tube is the beginning of both structures, and neurons are the building blocks of both structures. Retinal ganglionic cells, also known as RGCs, are a specific type of cell that are found in the retina. These cells are responsible for receiving light signals from the environment around them and then transmitting them to photoreceptors, which are involved in the process of vision. The retina, which is found inside the eye, is responsible for converting light into electrical impulses, which are then sent to the brain through the optic nerve. Glaucoma, age-related macular degeneration (AMD), and diabetic retinopathy are only few of the eye illnesses that can be caused by chronic progressive neurodegeneration of the retina, which is more prevalent in older people. It is the elderly who are most likely to be affected by these eye disorders; nevertheless, younger people are also susceptible to them and may experience permanent vision loss or a reduction in their eyesight. In most cases, neurodegenerative disorders that are characteristic of CSN are characterised by common symptoms and a cause that is only partially understood. Although certain risk factors have been identified, they do not account for all instances. On the other hand, according to a number of studies, several illnesses of the central nervous system (CNS), such as Alzheimer's disease (AD) and Parkinson's disease (PD), which are responsible for a significant amount of mortality and morbidity on a global scale, display distinctive alterations at the ocular level. It is helpful to be aware of potential linkages in order to have a better understanding of the mechanics on which onset occurs. In addition, experts have not yet reached a consensus regarding the factors that are responsible for these various disorders. In this overview, the symptoms of ocular illnesses are discussed in detail, with a particular focus on the interaction between the brain and the eye. At some point in the future, a more in-depth understanding could be of assistance in the development of innovative treatments that could help reduce or prevent blindness and improve quality of life.